2016
DOI: 10.1098/rspb.2016.0095
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of the Scottish islands via long-distance Neolithic transport of red deer (Cervus elaphus)

Abstract: Red deer (Cervus elaphus) have played a key role in human societies throughout history, with important cultural significance and as a source of food and materials. This relationship can be traced back to the earliest human cultures and continues to the present day. Humans are thought to be responsible for the movement of a considerable number of deer throughout history, although the majority of these movements are poorly described or understood. Studying such translocations allows us to better understand ancie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 39 publications
1
24
0
1
Order By: Relevance
“…The arguments made here about numbers are, however, translatable to these other species, and since they are considerably smaller, only a single boatload of sheep or pigs need ever have set sail from Continental Europe to be the source of all British and Irish domesticates. It is of considerable interest, however, that there is now evidence for the movement of wild deer populations at the start of the Neolithic, as suggested for Ireland (Woodman and McCarthy 2003;Carden et al 2012) but also apparently taking place in Scotland (Stanton, Mulville, and Bruford 2016). It seems that the importation of new domesticates inspired people to move other species around as well.…”
Section: Discussionmentioning
confidence: 99%
“…The arguments made here about numbers are, however, translatable to these other species, and since they are considerably smaller, only a single boatload of sheep or pigs need ever have set sail from Continental Europe to be the source of all British and Irish domesticates. It is of considerable interest, however, that there is now evidence for the movement of wild deer populations at the start of the Neolithic, as suggested for Ireland (Woodman and McCarthy 2003;Carden et al 2012) but also apparently taking place in Scotland (Stanton, Mulville, and Bruford 2016). It seems that the importation of new domesticates inspired people to move other species around as well.…”
Section: Discussionmentioning
confidence: 99%
“…(), with red deer from these locations also presenting the lowest allelic richness of all Scottish red deer populations analyzed, suggesting that the red deer population on this island might have originated from a small number of individuals. A recent mtDNA survey of red deer from Scottish archaeological sites up to 7,500 years BP found that samples from the Outer Hebrides and Orkney (where they are now extinct) had haplotypes not found in the rest of Scotland and suggested that human‐mediated transfer from a source beyond Scotland was likely (Stanton et al., ). Together these observations suggest further work on the modern red deer of Harris and Lewis would be useful, in particular, a survey of mtDNA variation.…”
Section: Discussionmentioning
confidence: 99%
“…The same is true for many wild animal species: they are given short shrift in archaeological discussions of food even though in the past they made a significant contribution to human diet and were often translocated and managed alongside animals that became the true 'domesticates' (e.g. Vigne, Daujat and Monchot 2015;Carden et al 2012;Carden 2012;Stanton, Mulville and Bruford 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent zooarchaeological and genetic studies make clear that it was in the Neolithic that red deer and wild boar were first introduced to Ireland Carden 2012) and several Scottish Isles saw the importation of red deer (Mulville 2010;Stanton, Mulville and Bruford 2016). Some of these islands may have functioned as self-sustaining game reserves, the animals being left to roam and breed without fear of natural predation so that they could be hunted on occasions of human visitation.…”
Section: 000 Years Of Wild Foods In Englandmentioning
confidence: 99%